Volume-outcome relation for acute appendicitis: evidence from a nationwide population-based study. - Po-Li Wei (Public Library of Science (PLoS), 2012)
Background Although procedures like appendectomy have been studied extensively, the relative importance of each surgeon's surgical volume-to-ruptured appendicitis has not been explored. The purpose of this study was to investigate the rate of ruptured appendicitis by surgeon-volume groups as a measure of quality of care for appendicitis by using a nationwide population-based dataset. Methods We identified 65,339 first-time hospitalizations with a discharge diagnosis of acute appendicitis (International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) codes 540, 540.0, 540.1 and 540.9) between January 2007 and December 2009. We used "whether or not a patient had a perforated appendicitis" as the outcome measure. A conditional (fixed-effect) logistic regression model was performed to explore the odds of perforated appendicitis among surgeon case volume groups. Results Patients treated by low-volume surgeons had significantly higher morbidity rates than those treated by high-volume (28.1% vs. 26.15, p<0.001) and very-high-volume surgeons (28.1% vs. 21.4%, p<0.001). After adjusting for surgeon practice location, and teaching status of practice hospital, and patient age, gender, and Charlson Comorbidity Index, and hospital acute appendicitis volume, patients treated by low-volume surgeons had significantly higher rates of perforated appendicitis than those treated by medium-volume surgeons (OR = 1.09, p<0.001), high-volume surgeons (OR = 1.16, p<0.001), or very-high-volume surgeons (OR = 1.54, p<0.001). Conclusion Our study suggested that surgeon volume is an important factor with regard to the rate of ruptured appendicitis.